Understanding macroeconomics - Gowland, David (Hants, 1990)
This new textbook provides short non-technical summaries of important areas of economics, especially those where the alternative literature is either not easily accessible or else highly specialized. An important objective of the book is to provide an analysis of current economic policy. It successfully demonstrates that simple economic analysis can be brought to bear lucidly and penetratingly on economic problems. The result is a book which, for its concise and authoritative survey of major areas, will be an essential purchase for school and college economics teachers and their libraries. It will also prove invaluable to university and polytechnic students of economics seeking an introduction to the application of economic theory to the major problems facing economists today.
Keywords: Economics